Morphological and Genetic Identification of Fish Species of River Ravi, Pakistan - Eeman, Ayesha; Naz, Saima; Chatha, Ahmad Manan Mustafa; Iqbal, Syeda Saira (Current Trends in OMICS, 2024)
DNA barcoding is a method that examines a specific part of the mitochondrial genome known as the cytochrome c oxidase subunit I (COI) gene, for species identification and biodiversity studies. The current study assessed the effectiveness of using the COI gene for the identification of fish species by constructing a phylogenetic tree with the help of a reference database of fish from the Head Balloki, River Ravi, Pakistan. A total of 15 fish species were analyzed with a 685-base pair (bp) segment of the mitochondrial COI gene sequenced (or "barcoded") for each species. These species represented 15 genera, 10 families, and 6 orders. On average, the sequences were 630 base pairs long. In terms of base composition, the average T content was the highest, while the average G content was the lowest. The AT content (54.1%) was higher than the GC content (45.9%). An analysis of nucleotide pair frequencies across the dataset revealed that out of 685 sites, 385 (56.20%) were conserved within the sequence. Of the 685 sites, 294 sites (42.92%) were variable and 226 (33%) were parsimony informative, while 66 of 685 sites (9.64%) were singletons. In the dataset, transitional pairings (si= 64) were more common than trans-versional pairings (sv = 57), with a si/sv (R) ratio of 1.1. On average, there were 483 pairs where the nucleotides were the same (ii). The average frequencies of nucleotide bases in these sequences were as follows: T (28.8%), C (28.1%), A (25.3%), and G (17.8%). The average Kimura two-parameter (K2P) distances within species, families, and orders were 0.24±0.01%, 0.24±0.02%, and 0.24±0.01%, respectively. Although, each species has a distinct cox1 sequence, various species might occasionally have similar haplotypes. In order to investigate evolutionary links, the maximum likelihood analysis approach was merged with the barcode-based method. In line with the taxonomy categories, the phylogenetic tree generated various groupings that were verified. The current study showed that cox1 sequencing, or DNA barcoding, is a useful method to accurately identify fish species based on both genetic and morphological characteristics.